Newman et la Bible - Paul Vaiss (Revue LISA)
After his conversion in 1816, the young Newman was under the influence of evangelical teaching. He considered the Bible literally as the infallible Word of God, the only source of authority for the Christian in matters of doctrine and conduct. When he became a fellow of Oriel College, Oxford, he was taught by Hawkins, the Provost, that Christian doctrine is to be found in the traditions, creeds and formularies of the Church, the role of Scripture being confined to proving doctrine. It is clear that he did not adopt that view immediately. A close study of his unpublished sermons shows that the authority of the Bible kept its full sway over him for a long time to come. It was only on the eve of the Oxford Movement, in 1832, that he integrated Hawkins’ teaching. From then on, Newman’s spiritual itinerary was to be a quest for a final authority that would complement the Bible. On the other hand, confronted with the challenge posed by Science to Holy Scripture, he took a stand in a sermon of 1826 that he was to keep to the end of his life. He felt that there is no need to try and reconcile the Bible and Science. First because revealed religion has its own evidence, that is at least as strong as that of Science, second because scientific knowledge is so subject to change that it would be wasting one’s time and degrading to go about trying to accommodate religion to the theories of Science.